2018
DOI: 10.1097/aln.0000000000002357
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-based Total Intravenous Anesthesia Is Associated with Better Survival Than Desflurane Anesthesia in Colon Cancer Surgery

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Previous research has shown different effects of anesthetics on cancer cell growth. Here, the authors investigated the association between type of anesthetic and patient survival after elective colon cancer surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
178
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(195 citation statements)
references
References 46 publications
11
178
4
2
Order By: Relevance
“…Furthermore, although the MA technique was associated with a significant reduction in postoperative inflammatory markers, our results do not support our hypothesis that combining several anesthetics/analgesics with anti-tumor properties would be associated with improved survival. Our findings are also not consistent with those of other studies which have demonstrated a favorable association between opioid-sparing TIVA and cancer progression [14,16]. Among several other factors, the differences in our findings may be explained by the components of MA in our study, the aggressive nature of appendiceal carcinomatosis, or the slightly older and sicker demographic of our MA group.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Furthermore, although the MA technique was associated with a significant reduction in postoperative inflammatory markers, our results do not support our hypothesis that combining several anesthetics/analgesics with anti-tumor properties would be associated with improved survival. Our findings are also not consistent with those of other studies which have demonstrated a favorable association between opioid-sparing TIVA and cancer progression [14,16]. Among several other factors, the differences in our findings may be explained by the components of MA in our study, the aggressive nature of appendiceal carcinomatosis, or the slightly older and sicker demographic of our MA group.…”
Section: Discussioncontrasting
confidence: 99%
“…This may have been evidenced by the significantly higher risk of progression and death in the MA group in unadjusted models, which remained higher (although insignificant) in the adjusted models; perhaps an effect of our small sample size. That said, a somewhat similar observation could be made about the studies by Wigmore et al [14] and Wu et al [16]. In both studies, patients who received volatile-opioid anesthesia had higher ASA scores and more advanced disease, and demonstrated worse survival after PSM.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…versus 5.8%), and increased postoperative metastasis rate (43.5% versus 13.4%) than propofol anesthesia group regardless of tumor node metastasis (TNM) stages during the 10 years' follow-up. 50 Similarly, a retrospective cohort study uncovered that patients in desflurane anesthesia group had a worse outcome, such as higher mortality rate (75.0% versus 30.8%), distant metastasis (15.9% versus 5.5%) or a higher local recurrence (70.1% versus 37.8%), compared with propofol group in HCC patients who underwent hepatectomy during 10 years' follow-up. 51 In contrast, a clinical research found that epithelial ovarian cancer patients at stage III who were given desflurane were related to a less overall rate of recurrence during primary cytoreductive surgery compared with patients who were given sevoflurane.…”
Section: Vegf and Angiopoietin-1mentioning
confidence: 98%